Stable DNA heteroduplex formation catalyzed by the Escherichia coli RecA protein in the absence of ATP hydrolysis. - Menetski, J P (1990)
A question remaining to be answered about RecA protein function concerns the role of ATP hydrolysis during the DNA-strand-exchange reaction. In this paper we describe the formation of joint molecules in the absence of ATP hydrolysis, using adenosine 5'-[gamma-thio]triphosphate (ATP[gamma S]) as nucleotide cofactor. Upon the addition of double-stranded DNA, the ATP[gamma S]-RecA protein-single-stranded DNA presynaptic complexes can form homologously paired molecules that are stable after deproteinization. Formation of these joint molecules requires both homology and a free homologous end, suggesting that they are plectonemic in nature. This reaction is very sensitive to magnesium ion concentration, with a maximum rate and extent observed at 4-5 mM magnesium acetate. Under these conditions, the average length of heteroduplex DNA within the joint molecules is 2.4-3.4 kilobase pairs. Thus, RecA protein can form extensive regions of heteroduplex DNA in the presence of ATP[gamma S], suggesting that homologous pairing and the exchange of the DNA molecules can occur without ATP hydrolysis. A model for the RecA protein-catalyzed DNA-strand-exchange reaction that incorporates these results and its relevance to the mechanisms of eukaryotic recombinases are presented.